Heart rate training increase endurance, raise lactate threshold, and boost power - Benson, Roy (Human Kinetics, 2011)
If you're serious about your sport, you're serious about conditioning. Now, with one small device, you can apply the latest technology, science, and research to take the guesswork out of training, monitor progress, and see results. Heart Rate Training will show you how! From functions, features, and operational advice for your device to interpreting and applying the results, Heart Rate Training is a step-by-step guide to optimizing performance. You'll learn how, when, and why monitors can, and should, be incorporated into your workouts, training, and conditioning program to produce maximum results. In Heart Rate Training, authors Roy Benson and Declan Connolly show you how to determine deficiencies in training and performance, create targeted programs to increase endurance, raise lactate threshold, increase speed and power, and monitor your recovery between workouts. And the sample programs allow you to manipulate the training components to design a long-term training plan across eight endurance sports: walking, running, cycling, swimming, triathlon, rowing, cross-country skiing, and team sports. When you're ready to take training and performance to the next level, turn to Heart Rate Training and achieve your personal best.